CUSTOMER/SOCIETY INFLUENCE, APPLICATION OF ISO 14001 (REGULATION), ENVIRONMENTAL CONSERVATION COSTS, MORAL AND CORPORATE SOCIAL RESPONSIBILITY ON ENVIRONMENTAL MANAGEMENT ACCOUNTING PERFORMANCE - Anita Ghalda; Harti Budi Yanti (STMIK Widuri Jakarta, 2023)
With the existence of new learning in the field of environmental accounting and the importance of the environment for the community. Researchers made this study with the aim of examining the influence of Customers/Society, ISO 14001, Environmental and Moral Conservation Costs and Corporate Responsibility on Environmental Management Accounting Performance. Researchers used primary data collection techniques, where the respondents of this study were active employees in the manufacturing industry. The results of this study are Corporate Morale and Responsibility have a positive effect on Environmental Management Accounting Performance. Whereas Customers/Society, ISO 14001, and Environmental Conservation Costs have no effect on the Performance of Environmental Management Accounting. The researcher recommends for further research to further develop the research by adding samples and variables to further refine the research.